LIABILITY OF GOVERNMENT IN PUBLIC ADMINISTRATION: EXPERIENCE OF FOREIGN COUNTRIES (Conferencea, 2022)
Liability of the government to the parliament is the accountability of the executive power to the parliament in the implementation of the powers established by law in the system of separation of powers, and the constitutional obligation of the members of the government to respond individually and collegially through various legal instruments for their ruling activities.